2009
DOI: 10.1002/jbm.b.31505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low level capacitive‐coupled pulsed electric field stimulation on mineral profile of weight‐bearing bones in ovariectomized rats

Abstract: Mineral content, mineral composition, and crystalline pattern of bone in osteoporosis are different from those of normal individuals. Present management of bone mineral loss is rather unsatisfactory primarily because of socioeconomic factors and untoward effects of the treatment drugs. We report the efficacy of capacitive-coupled pulsed electric field (CCPEF) to prevent bone loss in an ovariectomized rat model of osteoporosis. One month postsurgery either leg was stimulated with CCPEF, whereas the other leg di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The principal endpoints include bone mineral content/density, and the content of calcium, phosphorus, and carbon, as well as mechanical properties. (Manjhi et al, 2009). …”
Section: Animal Experimentsmentioning
confidence: 99%
“…The principal endpoints include bone mineral content/density, and the content of calcium, phosphorus, and carbon, as well as mechanical properties. (Manjhi et al, 2009). …”
Section: Animal Experimentsmentioning
confidence: 99%
“…Following the experiments of DiCarlo et al26 on chick embryos exposed to radiation, the protection conferred by the magnetic fields appears to influence free radical scavenging. PEMF has a variety of biological effects, such as its effects on bone healing,27,28 pain relief,29 and the balance of the neuroendocrine system (including hormone production and melatonin levels) 30. PEMF has frequencies at the lower end of the electromagnetic spectrum (from 6 Hz to 500 Hz).…”
Section: Introductionmentioning
confidence: 99%
“…In 1953, Yasuda et al applied continuous electrical current to a rabbit femur for 3 weeks and demonstrated new bone formation around the cathode [44]. Since then, use of EFs for bone healing applications has been widely researched [45]. Capacitive coupling electric field (CCEF) and inductive coupling electromagnetic field (EMF) are also being used more frequently in recent years.…”
Section: Physical Stimulation For Bone Regeneration and Fracture Healingmentioning
confidence: 99%